2018
DOI: 10.3233/jad-170602
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid and Plasma Levels of Inflammation Differentially Relate to CNS Markers of Alzheimer’s Disease Pathology and Neuronal Damage

Abstract: Inflammatory markers have been shown to predict neurocognitive outcomes in aging adults; however, the degree to which peripheral markers mirror the central nervous system remains unknown. We investigated the association between plasma and CSF markers of inflammation, and explored whether these markers independently predict CSF indicators of Alzheimer’s disease (AD) pathology or neuronal damage. Plasma and CSF samples were analyzed for inflammatory markers in a cohort of asymptomatic older adults (n=173). CSF s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
59
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 53 publications
4
59
0
3
Order By: Relevance
“…However, in another study, IP-10 levels were not increased in the AD group [ 384 ]. In a recent study in asymptomatic older adults, increased levels of CSF IP-10 were associated with increased levels of CSF t-tau and p-tau [ 29 ].…”
Section: Inflammation/glial Activationmentioning
confidence: 99%
“…However, in another study, IP-10 levels were not increased in the AD group [ 384 ]. In a recent study in asymptomatic older adults, increased levels of CSF IP-10 were associated with increased levels of CSF t-tau and p-tau [ 29 ].…”
Section: Inflammation/glial Activationmentioning
confidence: 99%
“…Ademais, a desconfiguração da barreira hematoencefálica (BHE), proporcionada por mediadores inflamatórios como citocinas e fatores citotóxicos, conduz ao maior acúmulo vascular de placas amiloides e consequente lesão neuronal isquêmica. 7,8 Em investigação dos marcadores inflamatórios capazes de apontar as mudanças fisiológicas neurocognitivas em adultos idosos, Bettcher et al 15 apontaram a possibilidade de marcadores como o MIP-1β e Aβ42, dosados no plasma e líquido cefalorraquidiano, como sendo capazes de oferecer informações sobre o grau inflamatório da DA. 15 Outro argumento que sustenta a hipótese de níveis elevados de resposta inflamatória como fator contribuinte para DA é a correlação entre lesões cerebrais traumáticas e a elevação gradativa de proteínas β-amiloide e Tau hiperfosforilada, próprias da DA e do envelhecimento humano.…”
Section: Introductionunclassified
“…At the same time, over the last years, it has been repeatedly demonstrated that peripheral immune challenges as diverse as skin and gastrointestinal inflammation, viral and microbial infections, toxic exposures, gut dysbiosis, and inflammation associated with atherosclerosis and obesity, can remotely elicit activation of innate immunity in the CNS, thereby driving or priming CNS neuroinflammation, which in turn can lead to peripheral disorders and AD-like neuropathology in the aging brain [ 12 , 34 45 ]. Central and peripheral levels of inflammation have been linked to clinical outcomes in early-stage AD patients, and epidemiological studies suggest that elevation of inflammatory markers may be evident decades before the onset of clinical manifestations [ 46 , 47 ]. The mechanisms by which the chronic inflammation and/or dysregulated immune responses associated with AD risk factors may influence individual susceptibility to neuroinflammation and AD neuropathology have been recently reviewed [ 48 ].…”
Section: Introductionmentioning
confidence: 99%